Isolation and Characterization of Indigenous Acetobacter Strains from Cashew Apple and Their Potential Use in Vinegar Production - Yaya Anianhou Ouattara; Doudjo Soro; Kouakou Romain Fossou; Ahou Cinthia Ines Yebouet; Ismael Abraham Cissé; Dogbo Marius Akissi; Adolphe Zézé; Emmanuel Assidjo; Kouassi Benjamin Yao (Fermentation)
Côte d’Ivoire has the largest cashew tree cultivation area in the world, but the cashew apple produced is still underutilized despite its potential for industrial use. The present study aimed to isolate and identify acetic acid bacterial strains and assess their potential use for cashew apple-based vinegar production. Vinegar mother from fermented juice was used to isolate acetic acid bacteria on a standard glucose-based medium. Physiological and biochemical tests followed by 16S rRNA gene analysis and phylogeny were used for isolate characterization. Moreover, their acetic acid production capacity was assessed. As results, five strains of the Acetobacter genus were isolated. Phenotypic and phylogenetic analysis revealed that four of them, namely OYA2, OYA6, OYA9, and OYA10, belong to the A. tropicalis/A. senegalensis species complex with 99.7% or 100% similarity. The fifth strain, OYA7, being similar (99.7%) to A. syzygii. All the isolates were resistant to alcohol 15% (v/v) and grew well between pH 5.0 and 6.5. Their optimal growth temperatures varied between 27 °C and 37 °C, and only isolate OYA6 grew at a temperature of up to 40 °C. They produced vinegar with a yield (Yp/s, g/g) varying from 0.82 to 0.92, and acetic acid contents (g/L) of 80.67, 70.26, 70.11, 68.70 and 67.22 were obtained with OYA6, OYA7, OYA2, OYA10, and OYA9, respectively. Thus, the isolate OYA6 appeared as the best candidate for vinegar production, owing to its superior yield and thermotolerance abilities that need to be further explored for industry use.